MOLECULAR TYPING OF STREPTOCOCCUS PNEUMONIAE BY THE MULTIPLEX POLYMERASE CHAIN REACTION ASSAY IN ACCORDANCE TO THE PREVALENCE OF SEROTYPES IN THE RUSSIAN FEDERATION - N. M. Alyab'eva; T. A. Blinova; O. A. Ponomarenko; A. V. Lazareva; L. K. Katosova; N. A. Mayanskii ("Paediatrician" Publishers LLC, 2013)
Aim: to compare two methods of S. pneumoniae molecular typing: classic serological method and the multiplex polymerase chain reaction (M-PCR) assay modified in accordance to the date on the serotypes circulating in Russian Federation. Patients and methods: 420 pneumococcal isolates mainly from non-sterile loci were analyzed. After microbiological identification pneumococci were serologically typed with the means of specific antiserum produced by Staten Serum Institute (Denmark) in latex agglutination test and/or capsular swelling method. At the same time we performed series of the M-PCR, which consisted of 7 consecutive reactions at the most. Results: serotype was identified by the means of serological method in all 420 strains of S. pneumoniae; in total we determined 24 different serotypes. By the means of the M-PCR we succeeded in identification of 95% (399/420) examined strains, and 90% of them were typed during the first 3 reactions. All isolates failed to be typed by M-PCR (n =21) have serotypes not included into the composition of the M-PCR. The results of serological and molecular typing were identical in 99,2% (396/399) of the isolates; 3 strains showed contradictory results: serotype 19A was found on serological assay and serotype 19F - on PCR assay. Conclusions: the introduced modification of M-PCR allows correct identification of pneumococcal serotype more than in 90% of strains circulating in the Russian Federation, including all serotypes of pneumococcal polysaccharide conjugate vaccine.